ANALYSIS OF THE EFFECT OF NET PROFIT MARGIN, TOTAL ASSET TURNOVER, AND FINANCIAL LEVERAGE ON RETURN ON EQUITY (ROE) IN THE PHARMACEUTICAL INDUSTRY SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE - Jelita. S. Srirahayu Situmorang; William; Leami Manao; Nurhani Aviona; Jhon Winfri Sitohang; Nasib (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
The pharmaceutical industry in Indonesia plays a crucial role in maintaining public health and is a strategic part of the country's economy. This study examines ROE, net profit margin, total asset turnover, and financial leverage in pharmaceutical companies listed on the Indonesia Stock Exchange. This study is quantitative in nature. The research data were obtained from secondary sources. Out of a total of 10 pharmaceutical companies listed on the Indonesia Stock Exchange during the period 2016-2024, a sample of 5 companies was selected, with a sample observation of 45 data points. The research results indicate that the classical assumptions have been met. The partial t-test found that net profit margin significantly and positively affects return on equity (ROE) in the pharmaceutical industry listed on the IDX. Total asset turnover significantly and positively affects return on equity (ROE) in the pharmaceutical industry listed on the IDX. However, financial leverage does not significantly affect return on equity (ROE). Net profit margin, total asset turnover, and financial leverage all have a simultaneous effect on ROE (F-test). The adjusted R-square (R2) value is 0.906, or 90.6%, which indicates a significant impact on ROE, while the remaining 9.4% is attributed to other variables that influence ROE.